Penerapan Strategi Total Physical Response, Bernyanyi, Dan Permainan Edukatif Pada Pembelajaran Bahasa Arab Untuk Anak Usia Dini - Harmanto Raharjo; Nopri Dwi Siswanto (Insititut Agama Islam Negeri (IAIN) Curup, 2021)
Early childhood is an individual figure that is in the age range of 0-7 years where at this time is often referred to as the Golden Age. At this time adults play a very important role that provides stimulation in developing aspects of development. Therefore, the right start-up is needed so that children feel happy so that they can receive good learning. The research approach used in this research is a qualitative approach. The type of research is Library Research research. And this study uses descriptive qualitative analysis. There are several strategies that can be used, including by applying the TPR (Total physical response) learning model, which focuses on introducing them to Arabic vocabulary through speech and action. Furthermore, there is a method of singing that is very liked by all children so that they do not feel bored in doing an activity. And lastly by applying educational game methods that students hope to no longer feel bored with Learning Arabic. The purpose of this research is to find the right and relevant strategies in learning Arabic. The Results of the implementation of this strategy are able to stimulate early childhood in acquiring a second language, namely Arabic.